The EC's import policy for Textiles - Hans-Dieter Kuschel (Intereconomics, 1977)
In implementing the Multilateral Textile Agreement the European Community opted for the instrument of export self-restraint agreements which — in contrast to unilaterally imposed restrictions — may already be concluded before a threatening market disruption has actually materialized. On the other hand, the self-restraint agreements favour, in their present form, certain malpractices which have given rise to serious criticism.
Keywords: 330; Trade